2020
DOI: 10.1136/bmjsem-2020-000909
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sedentary behaviour and physical inactivity in the workplace: protocol for a review of systematic reviews

Abstract: Background and objectiveIncreasing rates of urbanisation have been accompanied by higher levels of sedentary behaviour (SB) and reduced physical activity (PA) worldwide. While physical inactivity has long been identified as a major risk factor for morbidity and mortality, increased concerns about the detrimental associations between SB and health has led to the development of many interventions aimed at reducing SB and/or promoting PA. Due to the prominence of sedentary time spent at work, the workplace has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The increased urbanization and technological advancements have been accompanied by a high prevalence of sedentary behaviour (SB) and physical inactivity (PI) worldwide, especially in the workplaces [ 1 , 2 ]. A recent review found that working adults spent about 60% of their waking time in SB and about 4% of the day in moderate to vigorous physical activity (PA) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased urbanization and technological advancements have been accompanied by a high prevalence of sedentary behaviour (SB) and physical inactivity (PI) worldwide, especially in the workplaces [ 1 , 2 ]. A recent review found that working adults spent about 60% of their waking time in SB and about 4% of the day in moderate to vigorous physical activity (PA) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%